Loss of Tree Biomass in Jure Landslide, Sindhupalchowk, Nepal - Acharya, Smrita; Khadka, Udhab Raj (Journal of Institute of Science and Technology, 2016)
Landslide causes massive loss of lives and properties along with intangible losses in mountainous regions. Yet such intangible losses in ecosystems are rarely considered. The present study assesses the tree biomass lost due to Jure landslide in Sindhupalchowk that destroyed 71 hectare of land. Altogether, 12 plots (250 m2) were sampled through systematic and purposive sampling technique. The total tree biomass was estimated using allometric equation. The study recorded 21 tree species in which Schimawallichiii (Korth.), Lagerstroemia parviflora (Roxb.), Shorea robusta (Gaertn.), Alnus nepalensis (D. Don), Phyllanthus emblica (Linn.) and Celtius australis (Linn.) were dominant. Schima wallichiii had the highest density (320 individual ha-1) and frequency (92%). The total biomass of tree species was 216 ton ha-1 in which Schima wallichiii constituted the highest total tree biomass (82 ton ha-1). In 71 ha landslide area, the landslide caused loss of 15,336 tons of total tree biomass, which equals to 56,283 tons CO2 equivalents. These findings are relevant for assessing post-landslide impacts on the mountain environment. Furthermore, to reduce carbon emissions resulting from forest loss, mitigation of landslide is crucial. Journal of Institute of Science and Technology Vol. 21, No. 1, 2016,Page: 65-70